Special report on French language health services planning in Ontario, 2009 - Boileau, François (Office of the French Language Services Commissioner, 2009)
In this special report, the Commissioner explains the import ance of integrating French services into health care planning in Ontario. Throughout this report, the Commissioner identifies the obligations and responsibilities of the key players in the health care system with respect to the delivery of French health services. Supporting and illustrating his remarks are comments and anecdotes from the Francophone community. He then presents his conclusions and recom mendations.

Rapport spécial sur la planification des services de santé en français en Ontario, 2009 - Boileau, François (COMMISSARIAT AUX SERVICES EN FRANÇAIS, 2009)
Le présent rapport spécial porte sur l’importance d’intégrer les services en français dans la planification des soins de santé en Ontario. Tout au long de son rapport, le commissaire expose les obligations et les responsabilités des principaux acteurs du système de santé en matière de prestation des services en français. Il appuie et ponctue ses propos avec des témoignages recueillis au sein de la population francophone de l’Ontario avant de finalement présenter ses conclusions et recommandations.